2017
DOI: 10.1007/s00701-017-3362-2
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of CT perfusion within 24 h after onset is associated with WFNS grade but not development of DCI in patients with aneurysmal SAH

Abstract: The current findings suggest that disturbance of CT perfusion soon after the onset is associated with the WFNS grade but not with the development of DCI. Delayed cerebral ischemia may be solely caused by cerebral vasospasm due to a clot in the cistern, but not associated with early brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…44 A recent study also failed to associate CT perfusion to DCI, but found an association of lower perfusion to lower neurological grade on admission. 45 Although we would expect to find higher TTP values in patients who ultimately develop DCI, we found a paradoxical decrease of TTP in those patients in the early phase of SAH, albeit not significant. One explanation could be a false positive finding, and a small number of patients with DCI in our sample; another explanation could be the presence of comorbidities, such as cardiac failure, that could affect the velocity of arrival of the contrast, although we have no data to support this.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…44 A recent study also failed to associate CT perfusion to DCI, but found an association of lower perfusion to lower neurological grade on admission. 45 Although we would expect to find higher TTP values in patients who ultimately develop DCI, we found a paradoxical decrease of TTP in those patients in the early phase of SAH, albeit not significant. One explanation could be a false positive finding, and a small number of patients with DCI in our sample; another explanation could be the presence of comorbidities, such as cardiac failure, that could affect the velocity of arrival of the contrast, although we have no data to support this.…”
Section: Discussioncontrasting
confidence: 58%
“…44 A recent study also failed to associate CT perfusion to DCI, but found an association of lower perfusion to lower neurological grade on admission. 45…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MTT, T max maps are obtained following deconvolution of an automated or user‐defined proximal arterial input function from the tissue time‐attenuation course to isolate a hypothetical tissue impulse response, 19 providing an estimation of macrovascular delay while removing confounds related to the bolus injection or to more proximal (eg, extracranial) sources of delay. A prior study by Takahashi et al demonstrated that whereas prolonged MTT in patients with aSAH was associated with changes in World Federation of Neurological Societies grade, there was no difference in average MTT between patients who developed delayed cerebral infarction (DCI) and those who did not 26 ; thus we felt a contemporary investigation into the utility of T max in this setting to be timely.…”
Section: Discussionmentioning
confidence: 87%
“…The relatively small sample size of 31 patients should also be considered when interpreting our results, although our study population was larger than the sample size of the majority of prior studies (range 2–41 patients). 9 , 25 , 26 The study population is somewhat unique in that all patients had a CTA, CTP, and DSA within a 24‐hour window. In addition, we evaluated our results both on a per‐study and a per‐vessel level, the latter of which increased the sample size to a more robust 540 segments.…”
Section: Discussionmentioning
confidence: 99%
“…It corroborates with the previous report of our group suggesting that the development of vasospasm after aSAH may be determined solely by the presence of blood clots in the subarachnoid cisterns and not associated with the primary brain injury after aneurysm rupture. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%